MARKETING OF COMMUNICATION MADDOG DISTRO IN SHAPING CONSUMER BEHAVIOR - Kusumo, Chrysto Naru (Transformasi, 2015)
The research results show that of marketing communications conducted of distro Maddog, amongothers via the print media in the form of a leaflets, pamphlets, posters, banners, and online media (facebook, twiter and website ). In addition also to promote by buy one get one (bought one, get onefree), on Holidays and End Year consumers obtain as a price special or discount reach 20 % to 50 %purchase of products Maddog . Maddog Distro also promoting the product by follow exhibitions andbecome sponsorship of many events able to support that sales promotions, as well as Maddog Distrohas always maintained the quality of their products. Marketing communications conducted byMaddog Distro have formed 2 ( two ) consumer behavior, namely decisions making complex andloyal. Consumer behavior type complex making this decision, before transact/purchases in MaddogDistro, First search the information product to bought. Whereas the consumer behavior type is Loyal,consumers always suitable to the products bought of Maddog Distro product without seekinginformation from place and buy repeatedly.Key Word: Marketing of communications and behavior consumers